2019
DOI: 10.1007/s10461-019-02626-1
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of eHealth Interventions Addressing HIV/STI Prevention Among Men Who Have Sex With Men

Abstract: A systematic review was conducted to summarize and appraise the eHealth interventions addressing HIV/STI prevention among men who have sex with men (MSM), and characterize features of successful eHealth interventions. Fifty-five articles (17 pilots and 38 full efficacy trials) were included with the predominance of web-based interventions in the United Statesbased settings. Intervention modalities include web-based, short message service (SMS)/text messges/email reminder, online video-based, computer-assisted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 113 publications
(317 reference statements)
1
45
0
4
Order By: Relevance
“…In our home-care programme, home sampling is combined with eHealth technologies, which means that semiautomatic and semi-tailored text messages methods are used to improve response and enable better patient management. A large body of evidence has emerged displaying the effectiveness of text messaging in HIV/STI control [15]. The programme offers high-quality regular STI clinic care, and testing is linked to STI treatment, HIV care referral, partner notification, and sexual health counselling.…”
Section: Introductionmentioning
confidence: 99%
“…In our home-care programme, home sampling is combined with eHealth technologies, which means that semiautomatic and semi-tailored text messages methods are used to improve response and enable better patient management. A large body of evidence has emerged displaying the effectiveness of text messaging in HIV/STI control [15]. The programme offers high-quality regular STI clinic care, and testing is linked to STI treatment, HIV care referral, partner notification, and sexual health counselling.…”
Section: Introductionmentioning
confidence: 99%
“…Employing patient navigators within medical and nonmedical services improves linkage to and retention in HIV care for people living with HIV [ 10 ]. Web-based interventions that aim to improve health outcomes around sensitive and stigmatizing issues such as sexual health and HIV are also increasingly being utilized [ 16 , 17 ]. PleasePrEPMe implemented a bilingual online program for people to access confidential, sex-positive, free HIV-prevention information and health care navigation services, with the goal to decrease the rate of new HIV infections [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a web-based self-help intervention supplemented by brief chat counseling was shown to be an effective alternative to in-person counseling in supporting people with cannabis-use problems [ 15 ]. A systematic review [ 16 ] showed that electronic health interventions that address the prevention of HIV and other sexually transmitted infections (STIs) among men who have sex with men are impactful on changing short-term behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal design of eHealth intervention requires an in-depth investigation of the preference of the target group for the interventions' content, presentation and visualization method. Previous reviews indicated the advantages and disadvantages of different eHealth interventions on MSM, which highly depended on study settings [37,39]. In addition, understanding the patterns of electronic devices use, desired contents or functionality, as well as the unmet needs of the target population, is vital to develop successful interventions [47].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it can facilitate interventions’ accessibility given that MSM can access the intervention from almost anywhere over the Internet, at any time convenient, with a high sense of confidentiality, which is particularly important for MSM in places where homosexuality are stigmatized and/or criminalized [ 36 , 37 ]. Moreover, MSM can easily connect with their community, MSM-friendly organizations or qualified health professionals by distance via chatrooms, social network applications or text messages [ 38 , 39 ]. Evidence in worldwide has shown positive effects of eHealth interventions on promoting HIV/STI knowledge, increasing rates of condom use and HIV/STIs testing, as well as enhancing antiretroviral treatment adherence [ 40 42 ], which are comparable to the face-to-face approach [ 25 ].…”
Section: Introductionmentioning
confidence: 99%